Endocrine care of transpeople part II. A review of cross‐sex hormonal treatments, outcomes and adverse effects in transwomen. (25th March 2015) - Meriggiola, Maria Cristina; Gava, Giulia
Summary The treatment of transwomen relies on the combined administration of anti‐androgens or GnRH analogues to suppress androgen production and thereby reduce male phenotypic characteristics together with oestrogens to develop female characteristics. In transwomen, synthetic oestrogens such as ethinyl oestradiol, as well as conjugated equine oestrogens (CEE), should be avoided to minimize thromboembolic risks especially in older transwomen and in those with risk factors. Currently, available short‐ and long‐term safety studies suggest that cross‐sex hormonal therapy (CHT) can be considered safe in transwomen improving the well‐being and quality of life of these individuals. Long‐term monitoring should aim to decrease cardiovascular risks and should include prostate and breast cancer screenings.